Arquivos judiciários: uma proposta de organização do acervo de caráter permanente - Fontes, Patricio da Silva (2010)
Proposes a standardized organization for the permanent archive of the Judicial System in the state of Paraíba concerning to the First Jurisdiction. Our work has as justification the lack of standardization of the of the judicial system documental archive organization. This is an exploratory, descriptive and qualitative research which uses documental and bibliographic research techniques, participative observation, interviews, questionnaires, and a diagnosis of the archive. The context of the research is the judicial archives of the first jurisdiction of the judicial system of the state of Paraíba. The work is a case study taken place at the forum in the district of Santa Rita. The characterization of the archives and the identification of the record type existing in the district shows the inexistence of a pattern in the archive organization, and the importance of the judicial archive as a primary source of research, considering that the judicial archive is a place of memories of the institution and of the state of Paraíba society with a relevant social function. The research result generates an organization propose to the judicial archive from Paraíba based on a Record Classification Plan and on a Classification Scheme, to be applied in the referred archives, as well as some technical recommendations for the judicial archive to meet satisfactorily its users needs.